Microwave-assisted multicomponent reactions in heterocyclic chemistry and mechanistic aspects - Gulati, Shivani; John, Stephy Elza; Shankaraiah, Nagula (Beilstein Journal of Organic Chemistry, 2021)
Microwave-assisted (MWA) multicomponent reactions (MCRs) have successfully emerged as one of the useful tools in the synthesis of biologically relevant heterocycles. These reactions are strategically employed for the generation of a variety of heterocycles along with multiple point diversifications. Over the last few decades classical MCRs such as Ugi, Biginelli, etc. have witnessed enhanced yield and efficiency with microwave assistance. The highlights of MWA-MCRs are high yields, reduced reaction time, selectivity, atom economy and simpler purification techniques, such an approach can accelerate the drug discovery process. The present review focuses on the recent advances in MWA-MCRs and their mechanistic insights over the past decade and shed light on its advantage over the conventional approach.
Keywords: cycloaddition; Knoevenagel condensation; Michael addition; microwave; multicomponent reactions

(untitled) - Varma, R. S. (Green Chem., 1999)

(untitled) - Kamal, A.; Srinivasulu, V.; Seshadri, B. N.; Markandeya, N.; Alarifi, A.; Shankaraiah, N. (Green Chem., 2012)

(untitled) - Colacino, E.; Lamaty, F.; Martinez, J.; Parrot, I. (Tetrahedron Lett., 2007)

Microwave-Assisted Synthesis of Heterocycles - Bagley, M. C.; Lubinu, M. C. (Microwave-Assisted Multicomponent Reactions for the Synthesis of Heterocycles, 2006)

Microwaves in Organic and Medicinal Chemistry - Kappe, C. O.; Stadler, A. (Wiley-VCH, 2005)

(untitled) - Wang, X.; Xu, X.-P.; Wang, S.-Y.; Zhou, W.; Ji, S.-J. (Org. Lett., 2013)

(untitled) - Lei, M.; Song, W.-Z.; Zhan, Z.-J.; Cui, S.-L.; Zhong, F.-R. (Lett. Org. Chem., 2011)

(untitled) - Elders, N.; van der Born, D.; Hendrickx, L. J. D.; Timmer, B. J. J.; Krause, A.; Janssen, E.; de Kanter, F. J. J.; Ruijter, E.; Orru, R. V. A. (Angew. Chem., Int. Ed., 2009)
Angew. Chem. 2009, 121, 5970–5973. doi:10.1002/ange.200902683

(untitled) - Abdelraheem, E. M. M.; Shaabani, S.; Dömling, A. (Drug Discovery Today: Technol., 2018)

(untitled) - Zarganes-Tzitzikas, T.; Dömling, A. (Org. Chem. Front., 2014)

(untitled) - Sunke, R.; Babu, P. V.; Yellanki, S.; Medishetti, R.; Kulkarni, P.; Pal, M. (Org. Biomol. Chem., 2014)

(untitled) - Zarganes-Tzitzikas, T.; Neochoritis, C. G.; Dömling, A. (ACS Med. Chem. Lett., 2019)

(untitled) - Gedye, R.; Smith, F.; Westaway, K.; Ali, H.; Baldisera, L.; Laberge, L.; Rousell, J. (Tetrahedron Lett., 1986)

(untitled) - Giguere, R. J.; Bray, T. L.; Duncan, S. M.; Majetich, G. (Tetrahedron Lett., 1986)

(untitled) - Kuhnert, N. (Angew. Chem., Int. Ed., 2002)
Angew. Chem. 2002, 114, 1943–1946. doi:10.1002/1521-3757(20020603)114:11<1943::AID-ANGE1943>3.0.CO;2-P

Microwaves in Organic Synthesis - Loupy, A. (Wiley-VCH, 2006)

(untitled) - Kappe, C. O. (Angew. Chem., Int. Ed., 2004)

(untitled) - Glasnov, T. N.; Kappe, C. O. (Chem. – Eur. J., 2011)

(untitled) - Kappe, C. O. (Chem. Rec., 2019)

(untitled) - Priecel, P.; Lopez-Sanchez, J. A. (ACS Sustainable Chem. Eng., 2019)

Which microwave synthesis reactor is best one for your research?

(untitled) - Kremsner, J. M.; Kappe, C. O. (J. Org. Chem., 2006)

(untitled) - Obermayer, D.; Gutmann, B.; Kappe, C. O. (Angew. Chem., Int. Ed., 2009)
Angew. Chem. 2009, 121, 8471–8474. doi:10.1002/ange.200904185

(untitled) - Laxmikeshav, K.; Sakla, A. P.; Rasane, S.; John, S. E.; Shankaraiah, N. (ChemistrySelect, 2020)

(untitled) - Maddirala, A. R.; Andreana, P. R. (Eur. J. Org. Chem., 2016)

(untitled) - Tokala, R.; Bora, D.; Sana, S.; Nachtigall, F. M.; Santos, L. S.; Shankaraiah, N. (J. Org. Chem., 2019)

(untitled) - Sharma, P.; Reddy, T. S.; Kumar, N. P.; Senwar, K. R.; Bhargava, S. K.; Shankaraiah, N. (Eur. J. Med. Chem., 2017)

(untitled) - Nekkanti, S.; Veeramani, K.; Praveen Kumar, N.; Shankaraiah, N. (Green Chem., 2016)

(untitled) - Jiang, B.; Shi, F.; Tu, S.-J. (Curr. Org. Chem., 2010)

(untitled) - Kruithof, A.; Ruijter, E.; Orru, R. V. A. (Curr. Org. Chem., 2011)

(untitled) - Kumar Gupta, A.; Singh, N.; Nand Singh, K. (Curr. Org. Chem., 2013)

(untitled) - Kamanna, K.; Khatavi, S. Y. (Curr. Microwave Chem., 2020)

(untitled) - Fairoosa, J.; Saranya, S.; Radhika, S.; Anilkumar, G. (ChemistrySelect, 2020)

Green Sustainable Process for Chemical and Environmental Engineering and Science - Dolzhenko, A. V. (Microwave-assisted multicomponent reactions, 2021)

(untitled) - Soni, J. P.; Chemitikanti, K. S.; Joshi, S. V.; Shankaraiah, N. (Org. Biomol. Chem., 2020)

(untitled) - Gensicka-Kowalewska, M.; Cholewiński, G.; Dzierzbicka, K. (RSC Adv., 2017)

(untitled) - Nakhi, A.; Srinivas, P. T. V. A.; Rahman, M. S.; Kishore, R.; Seerapu, G. P. K.; Lalith Kumar, K.; Haldar, D.; Rao, M. V. B.; Pal, M. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Singh, S. K.; Singh, K. N. (J. Heterocycl. Chem., 2011)

(untitled) - Kumar, N. P.; Sharma, P.; Reddy, T. S.; Shankaraiah, N.; Bhargava, S. K.; Kamal, A. (Eur. J. Med. Chem., 2018)

(untitled) - Khurana, J. M.; Chaudhary, A.; Lumb, A.; Nand, B. (Green Chem., 2012)

(untitled) - Wang, S.-L.; Zhang, G.; Jie, D.; Jiang, B.; Wang, X.-H.; Tu, S.-J. (Comb. Chem. High Throughput Screening, 2012)

(untitled) - Matsuhisa, A.; Taniguchi, N.; Koshio, H.; Yatsu, T.; Tanaka, A. (Chem. Pharm. Bull., 2000)

(untitled) - Di Fabio, R.; Micheli, F.; Baraldi, D.; Bertani, B.; Conti, N.; Dal Forno, G.; Feriani, A.; Donati, D.; Marchioro, C.; Messeri, T.; Missio, A.; Pasquarello, A.; et al. (Farmaco, 2003)

(untitled) - Upadhyay, K.; Manvar, A.; Rawal, K.; Joshi, S.; Trivedi, J.; Chaniyara, R.; Shah, A. (Chem. Biol. Drug Des., 2012)

(untitled) - Mehta, V. P.; Modha, S. G.; Ruijter, E.; Van Hecke, K.; Van Meervelt, L.; Pannecouque, C.; Balzarini, J.; Orru, R. V. A.; Van der Eycken, E. (J. Org. Chem., 2011)

(untitled) - Wang, S.-L.; Cheng, C.; Wu, F.-Y.; Jiang, B.; Shi, F.; Tu, S.-J.; Rajale, T.; Li, G. (Tetrahedron, 2011)

(untitled) - Biswal, S.; Sahoo, U.; Sethy, S.; Kumar, H. K. S.; Banerjee, M. (Asian J. Pharm. Clin. Res., 2012)

(untitled) - Huang, L.; Zhang, X.; Li, J.; Ding, K.; Li, X.; Zheng, W.; Yin, B. (Eur. J. Org. Chem., 2014)

(untitled) - Lin, W.; Zheng, Y.-X.; Xun, Z.; Huang, Z.-B.; Shi, D.-Q. (ACS Comb. Sci., 2017)

(untitled) - Mali, P. R.; Chandrasekhara Rao, L.; Bangade, V. M.; Shirsat, P. K.; George, S. A.; Jagadeesh babu, N.; Meshram, H. M. (New J. Chem., 2016)

(untitled) - Mali, P. R.; Shirsat, P. K.; Khomane, N.; Nayak, L.; Nanubolu, J. B.; Meshram, H. M. (ACS Comb. Sci., 2017)

(untitled) - Bhandari, S.; Sana, S.; Sridhar, B.; Shankaraiah, N. (ChemistrySelect, 2019)

(untitled) - Kumar, D.; Sharma, P.; Singh, H.; Nepali, K.; Gupta, G. K.; Jain, S. K.; Ntie-Kang, F. (RSC Adv., 2017)

(untitled) - Thumar, N. J.; Patel, M. P. (ARKIVOC, 2009)

(untitled) - Wang, S.-L.; Wu, F.-Y.; Cheng, C.; Zhang, G.; Liu, Y.-P.; Jiang, B.; Shi, F.; Tu, S.-J. (ACS Comb. Sci., 2011)

(untitled) - Pérez-Sacau, E.; Soto-Delgado, J.; Estévez-Braun, A.; Ravelo, Á. G. (Tetrahedron, 2005)

(untitled) - Wu, Q.; Feng, H.; Guo, D.-D.; Yi, M.-S.; Wang, X.-H.; Jiang, B.; Tu, S.-J. (J. Heterocycl. Chem., 2013)

(untitled) - Sharma, S.; Sharma, K.; Ojha, R.; Kumar, D.; Singh, G.; Nepali, K.; Bedi, P. M. S. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Bhardwaj, V.; Gumber, D.; Abbot, V.; Dhiman, S.; Sharma, P. (RSC Adv., 2015)

(untitled) - Reddy, G. R.; Reddy, T. R.; Joseph, S. C.; Reddy, K. S.; Meda, C. L. T.; Kandale, A.; Rambabu, D.; Krishna, G. R.; Reddy, C. M.; Parsa, K. V. L.; Kumar, K. S.; Pal, M. (RSC Adv., 2012)

(untitled) - Kumar, S.; Verma, N.; Ahmed, N. (J. Saudi Chem. Soc., 2018)

(untitled) - Knorr, L. (Ber. Dtsch. Chem. Ges., 1884)

(untitled) - Paal, C. (Ber. Dtsch. Chem. Ges., 1885)

(untitled) - Dhinakaran, I.; Padmini, V.; Ganesan, K.; Selvarasu, K. (ChemistrySelect, 2017)

(untitled) - Sahu, M.; Siddiqui, N. (Int. J. Pharm. Pharm. Sci., 2016)

(untitled) - Saladino, R.; Ciambecchini, U.; Maga, G.; Mastromarino, P.; Conti, C.; Botta, M. (Bioorg. Med. Chem., 2002)

(untitled) - White, D. C.; Greenwood, T. D.; Downey, A. L.; Bloomquist, J. R.; Wolfe, J. F. (Bioorg. Med. Chem., 2004)

(untitled) - Scheringa, M.; IJzermans, J. N. M.; Jeekel, J.; Marquet, R. L. (Cancer Immunol. Immunother., 1990)

(untitled) - Sana, S.; Reddy, V. G.; Bhandari, S.; Reddy, T. S.; Tokala, R.; Sakla, A. P.; Bhargava, S. K.; Shankaraiah, N. (Eur. J. Med. Chem., 2020)

(untitled) - Biginelli, P. (Gazz. Chim. Ital., 1893)

(untitled) - Alvim, H. G. O.; de Lima, T. B.; de Oliveira, H. C. B.; Gozzo, F. C.; de Macedo, J. L.; Abdelnur, P. V.; Silva, W. A.; Neto, B. A. D. (ACS Catal., 2013)

(untitled) - Narahari, S. R.; Reguri, B. R.; Gudaparthi, O.; K., M. (Tetrahedron Lett., 2012)

(untitled) - Xavier, A. L.; Simas, A. M.; Falcão, E. P. d. S.; dos Anjos, J. V. (Tetrahedron Lett., 2013)

(untitled) - Kuraitheerthakumaran, A.; Pazhamalai, S.; Gopalakrishnan, M. (Arabian J. Chem., 2016)

(untitled) - Jarvis, M. F.; Yu, H.; McGaraughty, S.; Wismer, C. T.; Mikusa, J.; Zhu, C.; Chu, K.; Kohlhaas, K.; Cowart, M.; Lee, C.-H.; Stewart, A. O.; Cox, B. F.; et al. (Pain, 2002)

(untitled) - Pathania, S.; Rawal, R. K. (Eur. J. Med. Chem., 2018)

(untitled) - Buron, F.; Mérour, J. Y.; Akssira, M.; Guillaumet, G.; Routier, S. (Eur. J. Med. Chem., 2015)

(untitled) - Bruno, O.; Brullo, C.; Schenone, S.; Bondavalli, F.; Ranise, A.; Tognolini, M.; Impicciatore, M.; Ballabeni, V.; Barocelli, E. (Bioorg. Med. Chem., 2006)

(untitled) - Pedrola, M.; Jorba, M.; Jardas, E.; Jardi, F.; Ghashghaei, O.; Viñas, M.; Lavilla, R. (Front. Chem. (Lausanne, Switz.), 2019)

(untitled) - Naidu, P. S.; Bhuyan, P. J. (RSC Adv., 2014)

(untitled) - Taylor, E. C.; Liu, B. (J. Org. Chem., 2003)

(untitled) - El Kaïm, L.; Grimaud, L.; Wagschal, S. (Org. Biomol. Chem., 2013)

(untitled) - Karamthulla, S.; Jana, A.; Choudhury, L. H. (ACS Comb. Sci., 2017)

(untitled) - Zhang, Z.; Yuan, A.; Zheng, C. (Synth. Commun., 2018)

(untitled) - Insuasty, D.; Abonia, R.; Insuasty, B.; Quiroga, J.; Laali, K. K.; Nogueras, M.; Cobo, J. (ACS Comb. Sci., 2017)

(untitled) - Jiang, B.; Xue, L.-Y.; Wang, X.-H.; Tu, M.-S.; Liu, Y.-P.; Tu, S.-J. (Tetrahedron Lett., 2012)

(untitled) - Ueno, M.; Nabana, T.; Togo, H. (J. Org. Chem., 2003)

(untitled) - Wang, X.; Ma, L.; Yu, W. (Synthesis, 2011)

(untitled) - Bagdi, A. K.; Hajra, A. (Chem. Rec., 2016)

(untitled) - Prasad, P.; Kalola, A. G.; Patel, M. P. (New J. Chem., 2018)

(untitled) - Meanwell, N. A. (J. Med. Chem., 2011)

(untitled) - Kamal, A.; Shankaraiah, N.; Reddy, K. L.; Devaiah, V.; Juvekar, A.; Sen, S. (Lett. Drug Des. Discovery, 2007)

(untitled) - Chao, J.; Terkeltaub, R. (Curr. Rheumatol. Rep., 2009)

(untitled) - Itchaki, G.; Brown, J. R. (Ther. Adv. Hematol., 2018)

(untitled) - Dolzhenko, A. V.; Dolzhenko, A. V.; Chui, W.-K. (Heterocycles, 2006)

(untitled) - Dolzhenko, A. V.; Dolzhenko, A. V.; Chui, W.-K. (Heterocycles, 2008)

(untitled) - Dolzhenko, A. V.; Kalinina, S. A.; Kalinin, D. V. (RSC Adv., 2013)

(untitled) - Lalezari, I.; Nabahi, S. (J. Heterocycl. Chem., 1980)

(untitled) - Miyamoto, Y.; Yamazaki, C.; Matzui, M. (J. Heterocycl. Chem., 1990)

(untitled) - Lim, F. P. L.; Low, S. T.; Ho, E. L. K.; Halcovitch, N. R.; Tiekink, E. R. T.; Dolzhenko, A. V. (RSC Adv., 2017)

Recent Advances in Nucleosides: Chemistry and Chemotherapy - Seela, F.; Rosemeyer, H. (5-Aza-7-Deazapurines: Synthesis and Properties of Nucleosides and Oligonucleotides, 2002)

(untitled) - Agasimundin, Y. S.; Oakes, F. T.; Leonard, N. J. (J. Org. Chem., 1985)

(untitled) - Altaf, A. A.; Shahzad, A.; Gul, Z.; Rasool, N.; Badshah, A.; Lal, B.; Khan, E. (J. Drug Design Med. Chem., 2015)

(untitled) - Xie, W.; Wu, Y.; Zhang, J.; Mei, Q.; Zhang, Y.; Zhu, N.; Liu, R.; Zhang, H. (Eur. J. Med. Chem., 2018)

(untitled) - Desai, N. C.; Rajpara, K. M.; Joshi, V. V. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Chen, W.; Zhan, P.; Rai, D.; De Clercq, E.; Pannecouque, C.; Balzarini, J.; Zhou, Z.; Liu, H.; Liu, X. (Bioorg. Med. Chem., 2014)

(untitled) - Ansari, A.; Ali, A.; Asif, M.; Shamsuzzaman, S. (New J. Chem., 2018)

(untitled) - Duński, H.; Jóźwiak, W. K.; Sugier, H. (J. Catal., 1994)

(untitled) - Sorbera, L. A.; Castañer, J. (Drugs Future, 2003)

(untitled) - Ferraz, A. C.; Angelucci, M. E. M.; Da Costa, M. L.; Batista, I. R.; De Oliveira, B. H.; Da Cunha, C. (Pharmacol., Biochem. Behav., 1999)

(untitled) - Ando, M.; Wada, T.; Sato, N. (Org. Lett., 2006)

(untitled) - Conreaux, D.; Bossharth, E.; Monteiro, N.; Desbordes, P.; Balme, G. (Tetrahedron Lett., 2005)

(untitled) - Mekheimer, R. A.; Al-Sheikh, M. A.; Medrasi, H. Y.; Alsofyani, N. H. H. (Molecules, 2018)

(untitled) - Bai, H.; Sun, R.; Liu, S.; Yang, L.; Chen, X.; Huang, C. (J. Org. Chem., 2018)

(untitled) - Elhakmaoui, A.; Gueiffier, A.; Milhavet, J.-C.; Blache, Y.; Chapat, J.-P.; Chavignon, O.; Teulade, J.-C.; Snoeck, R.; Andrei, G.; De Clercq, E. (Bioorg. Med. Chem. Lett., 1994)

(untitled) - Trapani, G.; Franco, M.; Latrofa, A.; Carotti, A.; Serra, M.; Sanna, E.; Biggio, G.; Liso, G. (J. Med. Chem., 1999)

(untitled) - Bode, M. L.; Gravestock, D.; Moleele, S. S.; van der Westhuyzen, C. W.; Pelly, S. C.; Steenkamp, P. A.; Hoppe, H. C.; Khan, T.; Nkabinde, L. A. (Bioorg. Med. Chem., 2011)

(untitled) - Kamal, A.; Devaiah, V.; Reddy, K. L.; Rajendar; Shetti, R. V. C. R. N. C.; Shankaraiah, N. (J. Comb. Chem., 2007)

(untitled) - Kamal, A.; Shankaraiah, N.; Devaiah, V.; Reddy, K. L. (Tetrahedron Lett., 2006)

(untitled) - El-Sayed Ali, T. (Eur. J. Med. Chem., 2009)

(untitled) - Bhatt, A.; Singh, R. K.; Kant, R.; Chauhan, P. K. (Chem. Biol. Interface, 2016)

(untitled) - Maiti, B.; Chanda, K.; Selvaraju, M.; Tseng, C.-C.; Sun, C.-M. (ACS Comb. Sci., 2013)

(untitled) - Quiroga, J.; Trilleras, J.; Pantoja, D.; Abonía, R.; Insuasty, B.; Nogueras, M.; Cobo, J. (Tetrahedron Lett., 2010)

(untitled) - Jiang, B.; Liu, Y.-P.; Tu, S.-J. (Eur. J. Org. Chem., 2011)

(untitled) - Drizin, I.; Altenbach, R. J.; Buckner, S. A.; Whiteaker, K. L.; Scott, V. E.; Darbyshire, J. F.; Jayanti, V.; Henry, R. F.; Coghlan, M. J.; Gopalakrishnan, M.; Carroll, W. A. (Bioorg. Med. Chem., 2004)

(untitled) - Quiroga, J.; Portilla, J.; Serrano, H.; Abonía, R.; Insuasty, B.; Nogueras, M.; Cobo, J. (Tetrahedron Lett., 2007)

(untitled) - Chebanov, V. A.; Saraev, V. E.; Desenko, S. M.; Chernenko, V. N.; Knyazeva, I. V.; Groth, U.; Glasnov, T. N.; Kappe, C. O. (J. Org. Chem., 2008)

(untitled) - Jiang, B.; Ye, Q.; Fan, W.; Wang, S.-L.; Tu, S.-J.; Li, G. (Chem. Commun., 2014)

(untitled) - Kumar, S.; Bawa, S.; Gupta, H. (Mini-Rev. Med. Chem., 2009)

(untitled) - Marella, A.; Tanwar, O. P.; Saha, R.; Ali, M. R.; Srivastava, S.; Akhter, M.; Shaquiquzzaman, M.; Alam, M. M. (Saudi Pharm. J., 2013)

(untitled) - Afzal, O.; Kumar, S.; Haider, M. R.; Ali, M. R.; Kumar, R.; Jaggi, M.; Bawa, S. (Eur. J. Med. Chem., 2015)

(untitled) - Kulkarni, A.; Török, B. (Green Chem., 2010)

(untitled) - Andriushchenko, A. Y.; Desenko, S. M.; Chernenko, V. N.; Chebanov, V. A. (J. Heterocycl. Chem., 2011)

(untitled) - Khumalo, M. R.; Maddila, S. N.; Maddila, S.; Jonnalagadda, S. B. (RSC Adv., 2019)

(untitled) - Khan, I.; Ibrar, A.; Ahmed, W.; Saeed, A. (Eur. J. Med. Chem., 2015)

(untitled) - Donthiboina, K.; Mani, G. S.; Shankaraiah, N.; Kamal, A. (ChemistrySelect, 2020)

(untitled) - Kshirsagar, U. A. (Org. Biomol. Chem., 2015)

(untitled) - Rocchi, D.; González, J. F.; Menéndez, J. C. (Green Chem., 2013)

(untitled) - Burns, N. Z.; Baran, P. S.; Hoffmann, R. W. (Angew. Chem., Int. Ed., 2009)

(untitled) - Sawant, S. D.; Srinivas, M.; Reddy, G. L.; Rao, V. V.; Singh, P. P.; Vishwakarma, R. A. (Tetrahedron Lett., 2012)

(untitled) - Sadhu, C.; Dick, K.; Treiberg, J.; Sowell, C. G.; Kesicki, E. A.; Oliver, A. (Inhibitors of human phosphatidyl-inositol 3-kinase delta, 2001)

(untitled) - Gajaganti, S.; Kumari, S.; Kumar, D.; Allam, B. K.; Srivastava, V.; Singh, S. (J. Heterocycl. Chem., 2018)

(untitled) - Heravi, M. M.; Derikvand, F.; Ranjbar, L. (Synth. Commun., 2010)

(untitled) - Maleki, A.; Aghaei, M.; Ghamari, N. (Chem. Lett., 2015)

(untitled) - El-Gohary, N. S.; Shaaban, M. I. (Eur. J. Med. Chem., 2013)

(untitled) - Ahmadi, A.; Saidi, K.; Khabazzadeh, H. (Mol. Diversity, 2009)

(untitled) - Narayan, S.; Muldoon, J.; Finn, M. G.; Fokin, V. V.; Kolb, H. C.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2005)
Angew. Chem. 2005, 117, 3339–3343. doi:10.1002/ange.200462883

(untitled) - Wadhwa, P.; Kaur, T.; Singh, N.; Singh, U. P.; Sharma, A. (Asian J. Org. Chem., 2016)

(untitled) - Reddy, G. R.; Reddy, T. R.; Chary, R. G.; Joseph, S. C.; Mukherjee, S.; Pal, M. (Tetrahedron Lett., 2013)

(untitled) - Dheer, D.; Singh, V.; Shankar, R. (Bioorg. Chem., 2017)

(untitled) - Shankaraiah, N.; Sakla, A. P.; Laxmikeshav, K.; Tokala, R. (Chem. Rec., 2020)

(untitled) - Shankaraiah, N.; Kumar, N. P.; Tokala, R.; Gayatri, B. S.; Talla, V.; Santos, L. S. (J. Braz. Chem. Soc., 2019)

(untitled) - Mahmoud, A. G.; Guedes da Silva, M. F. C.; Sokolnicki, J.; Smoleński, P.; Pombeiro, A. J. L. (Dalton Trans., 2018)

(untitled) - Naeimi, H.; Nejadshafiee, V.; Masoum, S. (Appl. Organomet. Chem., 2015)

(untitled) - Somagond, S. M.; Kamble, R. R.; Shaikh, S. K. J.; Bayannavar, P. K.; Joshi, S. D. (ChemistrySelect, 2018)

(untitled) - Kashyap, S. J.; Garg, V. K.; Sharma, P. K.; Kumar, N.; Dudhe, R.; Gupta, J. K. (Med. Chem. Res., 2012)

(untitled) - Wagare, D. S.; Netankar, P. D.; Shaikh, M.; Farooqui, M.; Durrani, A. (Environ. Chem. Lett., 2017)

(untitled) - Mamidala, S.; Aravilli, R. K.; Vaarla, K.; Vedula, R. R. (ChemistrySelect, 2019)

(untitled) - Costa, M.; Dias, T. A.; Brito, A.; Proença, F. (Eur. J. Med. Chem., 2016)

(untitled) - Zarnegar, Z.; Safari, J. (New J. Chem., 2016)